Sistem Layanan Metrologi Legal Terpusat Berbasis Web - Kusuma, Andriansyah Perdana; Anshori Aris Widya, Moh.; Hariono, Tholib (Green Publisher Indonesia, 2024)
The development of information technology, especially in data management, can have a significant impact on improving efficiency and effectiveness in legal metrology services. Technological transformation not only changes how information is obtained but also fundamentally alters service systems for the public. A centralized web-based Legal Metrology Service System is being developed to streamline administrative data management and enhance services for individuals applying for metrological calibration and re-verification. Therefore, this system is designed using the waterfall method, ensuring each development stage, from needs analysis to implementation and maintenance, is conducted in a structured and systematic manner. The primary objective of this research is to improve the quality of calibration and re-verification services in Legal Metrology at the Office of Trade and Industry in Jombang Regency. With this system in place, it is expected that administrative processes and data management in legal metrology will operate more effectively and efficiently, thereby delivering better services to the public.